Liver fat in obesity: role of type 2 diabetes mellitus and adipose tissue distribution - Bozzetto, Lutgarda; Prinster, Anna; Mancini, Marcello; Giacco, Rosalba; De Natale, Claudia; Salvatore, Marco; Riccardi, Gabriele; Rivellese, Angela A.; Annuzzi, Giovanni (European journal of clinical investigation, 2011)
Eur J Clin Invest 2010; 41 (1): 39–44 Background  Fatty liver is commonly associated with insulin‐resistant conditions, often related to increased abdominal visceral fat. Our objective was to elucidate the specific roles of obesity, type 2 diabetes mellitus, insulin‐resistance and abdominal fat distribution. Materials and methods  The study population comprised 13 diabetic obese (DO), 10 nondiabetic obese (NDO), and nine normal‐weight control (C) men aged 28–65 years, with normal plasma triglyceride levels. DO were in good glycaemic control (HbA1c = 6·8 ± 0·8%) (M ± SD) with diet (n = 8) or diet + metformin (n = 5). Liver fat content was measured by 1H‐magnetic resonance spectroscopy, abdominal fat distribution by magnetic resonance imaging and insulin sensitivity by hyperinsulinaemic euglycaemic clamp. Results  DO and NDO subjects had similar whole‐body insulin resistance, BMI and waist circumference, higher than those of C subjects (P < 0·001). DO had more liver fat (11·9 ± 7·0%) than NDO (5·2 ± 2·8%, P < 0·05) and C (1·6 ± 1·0%, P < 0·001). Abdominal fat was greater in DO and NDO than in C (visceral: DO 3184 ± 843, NDO 2843 ± 1378 vs. C 1212 ± 587 cm3, P < 0·001; subcutaneous: DO 4029 ± 362, NDO 5197 ± 1398 vs. C 2312 ± 626 cm3, P < 0·001), visceral fat being not significantly different between the two obese groups, and subcutaneous fat significantly less in DO than in NDO (P < 0·05). Conclusions  Type 2 diabetes is associated with increased fat accumulation in the liver, independent of obesity and whole‐body insulin resistance. The increased liver fat in DO patients may be part of an altered regional fat distribution that includes an inadequate subcutaneous fat storing capacity, rather than simply being a consequence of increased abdominal visceral content.